Strategies for Avoiding Elementary School Students from Radicalism in Integrated Islamic Elementary School in West Sumatera - Zulmuqim Zulmuqim; Zainimal Zainimal; Mahmud Mahmud; Muhammad Zalnur; Adriantoni Adriantoni; Puti Andam Dewi (Institut Agama Islam Negeri Imam Bonjol Padang, 2022)
The Integrated Islamic Elementary School curriculum is considered exclusive, such as rejecting the ideology of other religions, claims of separation between Islam and the state and even believing in the government's evil conspiracy. Eradication of radicalism in schools is intended to narrow the space for movement, therefore the role of Integrated Islamic Elementary Schools (IIES) is very important in breaking away from the notion of radicalism. This study was conducted to answer the question of how the strategy of an integrated Islamic elementary school in integrating the curriculum, extracurricular activities, environmental creation and other activities to prevent radicalism is carried out. This is qualitative research with principals, teachers and students as the subject of documentation studies, and interviews, while data analysis is carried out with the stages of reduction, exploration, verification and contextualization of data. The result of this research is that research shows that the integration of the learning curriculum at IIES West Sumatra is divided into four types that strengthen the applicable curriculum for character strengthening, personal strengthening of students to face global challenges. Strategies in extracurricular activities are carried out with a structured and systematic pattern. The three strategies for creating the environment are pursued in an Islamic atmosphere, non-discriminatory, based on genetic characteristics, upholding ethical values, respecting cultural pluralism, and a polite culture for school members. The four strategies for routine, spontaneous and exemplary activities to prevent radicalism are carried out by strengthening character and integrating activities with learning activities, nurturing and habituation in the form of worship activities, order, neatness and cleanliness, eating and drinking. drinking, social behavior. So it can be concluded that there is no indication of the strengthening of radical ideology in IIES West Sumatra